2009
DOI: 10.1007/s11207-008-9311-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the 11-Year Solar Cycle on Variations of Cosmic Ray Intensity

Abstract: The monthly cosmic ray intensity (CRI) time series from Climax, Huancayo, Moscow, Kiel, and Calgary are used to investigate the presence of the 11-year periodic component with special attention paid to the solar influence on these variations. The results show obvious 11-year temporal characteristics in CRI variations. We also find a close anticorrelation between the 11-year solar cycle and CRI variations and time delays of the CRI relative to solar activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…We mention here only a few representative papers published in the last decade, e.g., Mursula, Zieger, and Vilppola (2003), Mavromichalaki et al (2003), Ruzmaikin, Cadavid, and Lawrence (2008), Kudela (2009), Ma, Han, andYin (2009), Chowdhury, Khan, andRay (2010), Sabbah and Kudela (2011), and references therein. The periodicities of the GCR intensity at first approximation can be divided into three groups: long-, intermediate-(mid-), and short-term quasi-periodicities (see, e.g., Chowdhury, Khan, and Ray, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We mention here only a few representative papers published in the last decade, e.g., Mursula, Zieger, and Vilppola (2003), Mavromichalaki et al (2003), Ruzmaikin, Cadavid, and Lawrence (2008), Kudela (2009), Ma, Han, andYin (2009), Chowdhury, Khan, andRay (2010), Sabbah and Kudela (2011), and references therein. The periodicities of the GCR intensity at first approximation can be divided into three groups: long-, intermediate-(mid-), and short-term quasi-periodicities (see, e.g., Chowdhury, Khan, and Ray, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The delay between the peaks in sunspot number and the consequent peaks in cosmic ray intensity ranges between 3-10 months (Ma et al, 2009), one year after the cosmic ray intensity peak is necessary to the plant for enhancing rhizome growth and energy storage, while another 7 months are required for the induction of flower development and fruit maturation (Gobert et al, 2001): the whole process may require a period between 22 and 30 months. Thus, from the beginning of the second summer after the solar activity peak, the plant is ready for sexual reproduction, and the warm conditions during the following months may just play the final regulatory role in order to ensure flower appearance at the end of the summer, as confirmed by the significant correlation found between flowering prevalence and mean summer air temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Peaks in solar activity show a periodicity of about 11-years (Ma et al, 2009); boosting cosmic and UV rays, they reduce cloud formation and runoff, and increase irradiance and Earth temperature (McCabe & Wolock, 2008). Increases of sea surface temperature linked to peaks in solar activity have been particularly evident (Southward et al, 1995;Roy & Haigh, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many advanced approaches using nonlinear analysis, such as those involving the wavelet transform methods, cross-recurrence plots (CRPs) and so on, are widely used to study the nonlinear behavior of solar activities. Over the last few years, there have been many applications with approaches of nonlinear analysis in scientific research, and they have been demonstrated to have unprecedented prowess in revealing hidden physical meanings in data (Frick et al 1997a,b;Grinsted et al 2004;Ma et al 2009;Johnson 2010;Gao et al 2011Gao et al , 2012Xie et al 2012;Li et al 2008Li et al , 2009bLi et al , 2010aLi & Liang 2010;and references therein).…”
Section: Introductionmentioning
confidence: 99%